270 Queen square test of auditory cognition (QSTAC): diagnosing dementia with sound. Issue 12 (14th November 2019) - Johnson, Jeremy CS; Hardy, Chris JD; Utoomprukporn, Nttawan; Rohrer, Jonathan D; Bamiou, Doris-Eva; Warren, Jason D
Abstract : Hearing impairment has emerged as a potent association of cognitive decline in dementia and a promising treatment target. To realise this promise, we need to resolve fundamental questions concerning the roles of peripheral versus central auditory deficits in different dementias, which hearing measures best capture cognitive symptoms and disability and whether hearing measures predict clinical course and brain atrophy. Using pre-existing and novel stimuli, created at the Dementia Research Centre, University College London, we have designed a unique test battery to assess central auditory function. This will be used to 'phenotype' central auditory dysfunction in Alzheimer's disease (AD) and the primary progressive aphasias (PPA) and compare them with controls as well as across disease groups. This will provide new tools to determine how auditory measures relate to clinical symptoms and daily-life disability and care burden. Using voxel-based morphometry (VBM) we also aim to correlate test measures with regional brain degeneration and measure how hearing deficits predict longitudinal clinical course. Here we present the make-up of the battery, explaining the motivation behind component tests and how they probe different stations of the auditory hierarchy. We also make predictions of likely group-specific outcomes, based on neuroanatomical disease predilection.